F.F. Incorporated. Makers of Freeze Dried Mango Powder - Nuguid, Reynaldo G.; De Jesus, Melvyn M.; Cimagala, Tristan A. (Diliman, Quezon City College of Engineering, 1971)
Name of plant: F. F. Incorporated (Filipinas Food Incorporated) Makers of freeze-dried mango powder -- Plant location: Zambales -- Fixed capital investment: 3,545,467 -- Break-even: 24% of the total capacity -- % return on investment before taxes: 20% -- Profit per year: 817,540
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Agricultural processing plants; Mango industry; Dried fruit